Features of Integrative Relations between Science, State and Industry in Russia and Abroad - Shinkevich, Alexey I.; Galimulina, Farida F.; Moiseyev, Vadim O.; Avilova, Vilora V.; Kuramshina, Kristina S.; Ishmuradova, Izida I.; Ponkratova, Liudmila A.; Grankina, Viktoriya L. (International Review of Management and Marketing, 2016)
The purpose of the article is to study the characteristics of the state stimulation of integrated cooperation of science and production in Russia and abroad, to identify problems in the different phases of the innovation process in the conditions of Russian reality. The leading method to the study of this issue is the method of systematization of Russian and foreign practices’ features of interaction between science and the state as well as revealing of institutional "traps" in the framework of the Russian innovation. The article presents the foreign and Russian practice of interaction between science and industry, reveals the national peculiarities of integrative relations between science and industry, as a result of research systematizes institutional "traps" at different stages of the innovation process in Russia and proposes measures to minimize them. Materials of the article are of practical value to public administration bodies in the development and implementation of Federal and regional programs of innovative development, development of innovation infrastructure, stimulation of innovative activity, the use of tools of technological platforms. Keywords: Integrative Interaction, Innovation Development, Modernization, Triple Helix, Institutional "Traps". JEL Classifications: F15, F42, F31